Deficiencies and Damages in Used Brick Buildings - Saparboyevich, Sattarov Ikramboy; Ikramboyevich, Sattarov Temur; o’g’li, Safarov Fazliddin Sattor (European Journal of Life Safety and Stability (2660-9630), 2022)
This article examines the causes of defects and damages in brick buildings which used at present time and their impact on the safety of building structures.